Penggunaan Multimetode dan Metode Ganda dalam Proses Pembelajaran Matakuliah Kewiraan - Suharjo Dwijosumarto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
The Use of Multimethods and Bimethods in the Teaching-Learning Process of Kewiraan. The study was intended to find out the effectiveness of using multimethods in the teaching-learning process of Kewiraan. Additionally, it was aimed at examining the differences between using multimethods and bimethods in terms of learning achievement. Data were collected through a test and observation, which were then analyzed using means and t-test. The results showed that multimethods could increased students' achievement.